Rotational Alignment of the Knee is Different in Osteological Specimens with and without a Large Cam Deformity of the Proximal Femur. Issue 4 (July 2017) - Gebhart, Jeremy J.; Streit, Jonathan J.; Goodman, Avi; Etscheidt, Jordan; Weinberg, Douglas S.; Bedi, Asheesh; Nho, Shane J.; Salata, Michael J.
Purpose: We studied a large osteological collection for differences in knee rotation based upon the presence or absence of a large cam deformity of the proximal femur. Methods: We obtained 357 matched tibiae and femora from the Hamann-Todd Osteological Collection and measured: femoral head-neck alpha angle, anteroposterior axis (or Whiteside's line) at the distal femur relative to the posterior condylar axis, and position of the tibial tubercle with respect to the posterior condylar axis of the proximal tibia. We then divided these specimens into two groups based upon alpha angle <45° (Group 1, n = 73) or alpha angle >60° (Group 2, n = 122) and performed an independent samples t -test to evaluate for differences in measured parameters between groups using this subset of specimens. Results: The mean alpha angles in Group 1 and 2 were 40.9° ± 3.3° and 67.0° ± 5.6°, respectively. Whiteside's line was externally rotated with respect to the posterior femoral condylar axis by a mean of 1.8° ± 6.8° in Group 1, vs. 3.0° ± 3.7° in Group 2 (p = 0.03). The tibial tubercle was externally rotated by a mean of 19.4° ± 6.8° in Group 1, versus 16.6° ± 5.1° in Group 2 (p = 0.003). Conclusions: Specimens with femoral head-neck alpha angle >60° demonstrated greater external rotation of the distal femur and a more internally-rotated tibial tubercle compared to specimens with an alpha angle <45°. Differences in anatomic characteristics of the knee may play a role in the development of patellofemoral pain in patients with a large cam deformity.